The Role of Plant Microbiomes in Sustainable Agriculture: A Paradigm Shift (International Journal of Food and Nutritional Sciences, 2021)
Plant microbiomes, comprising diverse microorganisms that live on and within plants, are pivotal to modern sustainable agricultural practices